MEMAKSIMALKAN LAHAN SEMPIT UNTUK MENGHASILKAN KARYA DAN BERTAHAN DI INDUSTRI FOTO PREWEDDING DI TENGAH PANDEMI COVID-19 - Tusana, Putu Andika Aries; Pemayun, Tjokorda Udiana Nindhia; Bratayadnya, Putu Agus (Lp2mpp Isi Denpasar - Ps. Fotografi, 2022)
This study discusses maximizing narrow land to produce works in the pre-wedding photo industry in the midst of the Covid-19 pandemic. During this Covid-19 pandemic, many photographers working in the pre-wedding photo industry did not get job because many locations that were often used as pre-wedding were closed due to the covid-19 pandemic. The formulation of the problem in this study discusses how to use narrow land as a location for pre-wedding photo shoots and the second is how the results of pre-wedding photos with locations that use narrow land. The purpose of this study is to find out and describe how to use narrow land as a location for pre-wedding and to find out the results of pre-wedding photos with locations that use narrow land. The study of sources used in this research are several books, journals and articles related to problems such as the use of narrow land, ways of working, and the creative industry. The theoretical basis used is the Aesthetic theory as the basis for studying the problem. The implementation method carried out during the research process is the observation, interviews, documentation and work practices as well several sources of data used, namely primary and secondary data. This research is presented in the form of narrative in the form of a thesis. The results of this study indicate that pre-wedding photos can not only be done in a large place. However, can also be done in a narrow land by maximizing it through ideas and creativity.